2011
DOI: 10.1097/jpn.0b013e3182259943
|View full text |Cite
|
Sign up to set email alerts
|

Informing Parents About the Actual or Impending Death of Their Infant in a Newborn Intensive Care Unit

Abstract: Modern perinatal and neonatal care practices have increased survival of infants that in previous care eras would have perished. The majority of infants admitted to a newborn intensive care unit following delivery currently do well and are discharged home. Unfortunately for others, the ultimate outcome may be death. The death of a newborn infant is clearly a devastating loss to parents. How parents are informed of their infant's actual or impending death can either add to a grief reaction, or help support paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 19 publications
0
46
0
4
Order By: Relevance
“…Most of them also find it helpful to share in decisions to withhold or withdraw lifesustaining treatment (LST), decisions that often precede a child's death. 2,3,5,9,11,[16][17][18][19][20] Parents' perception of a shared approach may even lower their grief in the long term. 21 The extent to which parents want to share in the decision-making process differs from parent to parent.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Most of them also find it helpful to share in decisions to withhold or withdraw lifesustaining treatment (LST), decisions that often precede a child's death. 2,3,5,9,11,[16][17][18][19][20] Parents' perception of a shared approach may even lower their grief in the long term. 21 The extent to which parents want to share in the decision-making process differs from parent to parent.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Many of the recommendations were developed by understanding parents' perspectives and what they perceive to be helpful or not during end-of-life care (Bruns and Steeples, 2001;Armentrout and Cates, 2011;Wocial, 2000). Overall it has been found that how information is communicated greatly influences parent's perspectives of their interactions with providers and their confidence and trust in the care they are receiving (Wocial, 2000;Ptacek and Eberhardt, 1996).…”
Section: Principles Of Effective Communication In the Nicumentioning
confidence: 97%
“…One of the cornerstones of familycentered care is effective communication and information exchange, which facilitates mutual understanding and collaborative decision making between parents and medical professionals, and ensures that care is responsive not only to the family's unique needs, circumstance, and values, but to the infant's best interests (Gooding et al, 2011;Bruns and Steeples, 2001;Carter and Maroney, 2003). Effective communication is particularly important in the delivery of difficult news as poor communication can add significantly to parents' feelings of grief (Armentrout and Cates, 2011;Laing and Freer, 2008). Unfortunately, training and strategies for effective communication with families are inconsistently implemented and many physicians feel poorly prepared to deliver bad news in the NICU (Harrison and Walling, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Communication skills should be included as part of the training of healthcare personnel, together with the clinical competence specific to each branch of the profession [36]. Such training can enhance empathy in carers, helping them evaluate patients' expectations, offer appropriate support, reduce emotional distress and foster compliance with clinical guidelines [26].…”
Section: Discussionmentioning
confidence: 99%